2015
DOI: 10.4236/ajps.2015.615248
|View full text |Cite
|
Sign up to set email alerts
|

Algae and Cyanobacteria in Soils of Moscow

Abstract: Algal-cyanobacterial communities, soil nano-and microfauna, and mycelium of micromycetes were studied in soils of an administrative district of Moscow. To characterize the habitat conditions of microbiota in the soils of different functional zones of the city, the acid-base conditions and the contents of exchangeable and water-soluble nitrogen, mobile heavy metals, and soluble salts were determined. The diversity of species of algal-cyanobacterial communities, the composition of the dominant species, the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…In the present study a lower level of biological activity in the urban soils was found (total of 16 species were isolated: Achnanthes lanceolata, Caloneis aerophila, C. bacillum, Chlorococcum sp., Navicula atomus, N.minima, Nitzschia pusilla, Pinnularia lagerstedtii, Pseudococcomyxa simplex, Scenedesmus rubescens, Scotiellopsis levicostata, Spongiochloris excentric, Stichococcus bacillaris, Stenomitos frigidus, Stigonema minutum, Tetracystis aeria, because urban soils are contaminated of heavy metals and sources are automobiles exhaust, sewage water, industrial aste, Batumi oil terminal et al Similar results were received by almost in yell, red and sod-podzolic soils that were receiving wastewater of Kintrishi and Chakvis ckali for several years. Practically similar results were obtained by various researchers [19,27,28,29,43].…”
Section: Resultssupporting
confidence: 89%
“…In the present study a lower level of biological activity in the urban soils was found (total of 16 species were isolated: Achnanthes lanceolata, Caloneis aerophila, C. bacillum, Chlorococcum sp., Navicula atomus, N.minima, Nitzschia pusilla, Pinnularia lagerstedtii, Pseudococcomyxa simplex, Scenedesmus rubescens, Scotiellopsis levicostata, Spongiochloris excentric, Stichococcus bacillaris, Stenomitos frigidus, Stigonema minutum, Tetracystis aeria, because urban soils are contaminated of heavy metals and sources are automobiles exhaust, sewage water, industrial aste, Batumi oil terminal et al Similar results were received by almost in yell, red and sod-podzolic soils that were receiving wastewater of Kintrishi and Chakvis ckali for several years. Practically similar results were obtained by various researchers [19,27,28,29,43].…”
Section: Resultssupporting
confidence: 89%
“…One of the most negative consequences of eutrophication is cyanobacteria proliferation and toxin release to surface waters [72]. However, microscopic algae and cyanobacteria are permanent components of terrestrial phytocenoses, where they form phototropic blocks of soil microbial cenoses and are dwellers in either natural or anthropogenically disturbed soils [73].…”
Section: Discussionmentioning
confidence: 99%
“…Their diversity and functioning can be significantly disturbed under the impact of urban factors. Data obtained by different researchers (Kabirov et al, 1997;Suhanova et al, 2000Suhanova et al, , 2011Sharipova et al, 2004;Rahmatullina et al, 2009;Aksenova et al, 2010;Shekhovtseva et al, 2010;Truhnitskaya et al, 2012;Dorokhova et al, 2015;Bachura et al, 2015;Antipina, 2016) indicates the presence of specific features in the algal composition of urboecosystems. It is determined by the peculiarities of anthropogenic inflluence on soils of urban areas.…”
Section: Discussionmentioning
confidence: 97%
“…The problem of soil algae diversity and ecology of urban areas has been raised in the works of various scientists outside Ukraine (Kabirov et al, 1997;Suhanova et al, 2000;Sharipova et al, 2004;Rahmatullina et al, 2009;Aksenova et al, 2010;Shekhovtseva et al, 2010;Suhanova et al, 2011;Truhnitskaya et al, 2012;Dorokhova et al, 2015;Bachura et al, 2015;Antipina, 2016). This has helped to reveal the certain regularities of urban soils and to outline the approaches for using them with a bioindicatory purpose.…”
Section: Introductionmentioning
confidence: 99%